The Typology of Verbal Form Plusquamperfect in Old Armenian, German and Latin - KHACHATRYAN, LALIK (Bulletin of Yerevan University B: Philology, 2021)
In Old Armenian, German and Latin Plusquamperfectum typologically is characterized with active-like and passive-like conjugations, different basic forms of stems, synthetic and analytic constructions in verbal paradigms, and with the functions of auxiliary verbs.
Keywords: plusquamperfectum, active-like conjugation, passive-like conjugation, typological characteristics, analytical type, synthetic type